Fluidization of gas-solid in atmospheric bubbling fluidized bed combustor - Permatasari, Rosyida (2014)
The fluidization behavior of a non-reactive gas-solid in the Atmospheric Bubbling Fluidized Bed Combustor (ABFBC) was studied. Experiments were conducted using laser based Particle Imaged Velocimetry (PIV) with B Geldart silica sand (diameter, Ø = 300 – 425 µm) in 2 m high cylindrical combustion chamber. The PIV was used to determine the particle velocity distribution in the combustion chamber. The experiments established the distribution of the sand along the height of the combustion chamber. Consequently, 3D CFD simulations were conducted using ANSYS FLUENT 13.0 software, of which their results were compared with the experimental counterpart. The comparison between the results of the developed CFD models and the experimental data showed very close agreement.